Correlación T-S de las masas de agua en la región del domo térmico de Costa Rica (ING) - Brenes, C. L. (1985)
Structure and water mass properties variations of Costa Rica Dome área, are studied according to T-S analytical relations. The Hydrographic stations correspond to Expeditions EASTROPIC (Feb-Ag.Set, 1967-Feb.1986) and CRUISES 075-076 of the R/V Thomas G. Thompson (Dec. 1972- Jan 1973) A review of the water mass classification reflects that the Equatorial Pacific Water Mass and Oxygen Minimum Layer correspond to the same water mass. The least Square Method is used for T-S curve polynomial fitting, in order to obtain the local T-S (T) relation.